2011
DOI: 10.1182/blood-2011-08-372649
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab blocks protective serologic response to influenza A (H1N1) 2009 vaccination in lymphoma patients during or within 6 months after treatment

Abstract: Cancer patients are often encouraged to receive seasonal influenza vaccination. The monoclonal antibody rituximab is widely used in treatment of non-Hodgkin lymphoma. This results in a prolonged depletion of normal B cells, which might impair humoral responses. The aim of the present study was to investigate whether lymphoma patients undergoing rituximab-containing treatment regimens or having received such regimens within the past 6 months were able to mount protective antibody responses to the influenza A(H1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
106
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(125 citation statements)
references
References 16 publications
12
106
0
7
Order By: Relevance
“…Recent studies have also shown the low immunogenicity of influenza vaccines in lymphoma patients and patients on rituximab treatment. [30][31][32][33][34][35][36][37][38][39][40][41][42][43] The results obtained by us here are in agreement with those findings. Subjects having pre-titer ≥ 1:10 did not show any increase in antibody response after the second vaccination.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Recent studies have also shown the low immunogenicity of influenza vaccines in lymphoma patients and patients on rituximab treatment. [30][31][32][33][34][35][36][37][38][39][40][41][42][43] The results obtained by us here are in agreement with those findings. Subjects having pre-titer ≥ 1:10 did not show any increase in antibody response after the second vaccination.…”
Section: Discussionsupporting
confidence: 83%
“…The inhibitory effect of rituximab on antibody induction has been reported by many, but we believe that ours is the first report that demonstrates this effect by eliminating the effect of the underlying disease (lymphoma), through multivariate logistic regression analysis. 19,[39][40][41][42] There is a possibility that the observed effect was related to the fact that the multivariate logistic regression analysis did not include Hodgkin's lymphoma. The Japanese population has fewer patients of Hodgkin's lymphoma than other populations, and our patients also did not have this disease.…”
Section: Discussionmentioning
confidence: 98%
“…Für Impfungen von Bedeutung ist die Verwendung von CD20-Antikörpern wie Rituximab oder Ofatumumab, die über zumindest drei verschiedene Mechanismen gleichzeitig wirken und zu einer B-Zell-Depletion führen [56]. Wichtig ist, dass ein Impfansprechen unter einer Anti-CD20-Therapie nicht gegeben ist, weil die Antikörper-bildenden B-Zellen fehlen [57,58]. Darüber hinaus kann eine Anti-CD20-Therapie zu einer Reaktivierung von Hepatitis B führen, die nicht selten fulminant verläuft [59].…”
Section: Diabetes Mellitusunclassified
“…Védőoltások alkalmazása rituximab kezelés mellett: humorális immunválasz csökkenésében a védőoltások kapcsán [33]. Ezt korábbi vizsgálatok is alátámasztják, melyben azt igazolták, hogy önmagában adott kemoterápia mellett kimutatható immunválasz a védőoltásokra, bár ennek mértéke elmarad az egészségesekétől [34].…”
Section: Progresszív Multifokális Leukoencephalopathia (Pml)unclassified